Analysis of Islamic Religious Education (PAI) Materials from the Perspective of Student Interests, Motivation and Talents - Hendra; Thobroni; Khozin; Hermansyah (al-Afkar, Journal For Islamic Studies, 2024)
Islamic religious education for students is very important because religion will guide, control and control all children's behavior. Because only religion can control and direct humans to the good path. So education and guidance regarding Islamic religious education must be more effective. This requires teachers to really understand the material or teaching materials that will be delivered. This research uses a qualitative methodology with a Literature Study approach, this approach is used to extract information from literature sources that are relevant to the research focus, both from books, journals and the results of previous research findings. The results of research on PAI material analysis illustrate that there are several important things for teachers to do, including; Gardening, Classifying or grouping learning materials based on relevant topics, themes or concepts. Second, choose the material that is most relevant and in accordance with the Graduate Competency Standards (SKL) and Competency Standards (SK) for Islamic Religious Education subjects by paying attention to students' conditions and interests, because quite a few teachers deliver material without understanding students' needs and desires. Third, Present the material in depth to the selected material and adapt it to the students' abilities. Fourth, teachers must also be careful in choosing the methods and strategies used when delivering teaching material, so that students can enjoy the learning process enthusiastically and pleasantly. Fifth, the teacher determines indicators of expected learning outcomes from the development of the material taught.